A path begins - White, J. A. (White, J. A. Thickety., 2015)
When Kara Westfall was six years old, her mother was convicted of the most heinous of crimes--witchcraft. Ever since then, Kara and her little brother Taff have lived on their own, shunned by the village. But when Kara follows a strange bird into the mysterious forest known as Thickety and finds a powerful book that may have belonged to her mother, she begins to realize that her mother's powers were more wondrous than she ever dreamed.